Sequence relationship of glycosylated and unglycosylated gag polyproteins of Moloney murine leukemia virus. - Edwards, S A (1980)
Both glycosylated and unglycosylated polyproteins coded by the gag gene are produced in cells infected with Moloney murine leukemia virus. GpP80gag is a glycosylated precursor of a larger gag glycoprotein exported to the cell surface, whereas Pr65gag is an unglycosylated precursor of the virion internal structural proteins. GpP80gag contains not only carbohydrate, but also additional polypeptide sequences not found in Pr65gag. In the experiment reported here, we localized the differences between GpP80gag and Pr65gag with respect to the domains of the individual gag proteins. This was done by comparison of partial proteolytic cleavage fragments from Pr65gag, from GpP80gag, and from the unglycosylated form of GpP80gag (P75gag) which had been immunoprecipitated by antisera specific for gag proteins p30, p15, and p10. We conclude that the additional polypeptide sequences in GpP80gag are located at or very near the amino terminus of the polyprotein. The carbohydrate in GpP80gag is attached to polypeptide sequences held in common between GpP80gag and Pr65gag.